Discovering Computers 2018 : Digital Technology, Data, and Devices - Vermaat, Misty E.: Susan L. Sebok, Steven M. : Freund, Jennifer T. : Campbell, Mark Frydenberg; Vermaat, Misty; Sebok, Susan L.; Freund, Steven M.; Campbell, Jennifer T.; Frydenberg, Mark (USA : Cengage Learning, 2018)
Teach students to maximize their use of mobile devices, make the most of online tools for collaboration and communication, and fully utilize today's Internet capabilities with the latest edition of DISCOVERING COMPUTERS 2018. Introductory computing students see how technology skills assist in employment and advancing their careers. This edition highlights today's most current technology trends and developments. Timely coverage now emphasizes web development, how to create a strong web presence, and take full advantage of latest Windows 10. The authors provide helpful suggestions for hands-on exercises, small group activities, and discussion topics that allow students to apply and demonstrate their understanding of each module. Self-assessments open each module and enable learners to focus their study and learn more in less time. DISCOVERING COMPUTERS presents the key content that students need for success, using an inviting approach that ensures understanding.
1. Introducing Today's Technologies: Computers, Devices, and the Web -- 2. Connecting and Communicating Online: The Internet, Websites, and Media -- 3. Computers and Mobile Devices: Evaluating Options for Home and Work -- 4. Programs and Apps: Productivity, Graphics, Security, and Other Tools -- 5. Digital Security, Ethics, and Privacy: Threats, Issues, and Defenses -- Focus On: Technology Timeline -- 6. Computing Components: Processors, Memory, the Cloud, and More -- 7. Input and Output: Extending Capabilities of Computers and Mobile Devices -- 8. Digital Storage: Preserving Content Locally and on the Cloud -- 9. Operating Systems: Managing, Coordinating, and Monitoring Resources -- 10. Communicating Digital Content: Wired and Wireless Networks and Devices -- 11. Building Solutions: Database, System, and Application Development Tools -- 12. Working in the Enterprise: Systems, Certifications, and Careers -- Focus On: Web Development -- Appendix A: Technology Acronyms -- Appendix B: Troubleshooting Computer and Mobile Device Problems.
Minimal Level Cataloging Plus.
Includes index.
Keywords: Computers; Electronic data processing; Internet; World Wide Web; Mobile computing; Computer science; Computer networks; Computer networks; Computer science; Computers; Electronic data processing; Internet; Mobile computing; World Wide Web